2009
DOI: 10.1002/mnfr.200800177
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetic and safety profile of trans‐resveratrol in a rising multiple‐dose study in healthy volunteers

Abstract: This was a double-blind, randomised, placebo-controlled study to investigate the pharmacokinetics and safety of trans-resveratrol. In four groups of ten healthy adult subjects (five males and five females), two subjects were randomized to receive placebo and eight subjects to receive trans-resveratrol 25, 50, 100 or 150 mg, six times/day, for thirteen doses. Peak plasma concentrations of trans-resveratrol were reached at 0.8-1.5 h postdose. Following the 13th dose of trans-resveratrol 25, 50, 100 and 150 mg, m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
280
3
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 403 publications
(314 citation statements)
references
References 20 publications
11
280
3
2
Order By: Relevance
“…Extremely rapid sulfate conjugation by the intestine/liver appears to be the ratelimiting step in t-RVT bioavailability. Second peak at 2 h indicates enterohepatic recirculation of the drug that has been well documented and enterohepatic recirculation is susceptible to circadian variation (Almeida et al, 2009) (as is evident from Figure 4 where two peaks of C max and T max were observed). A major portion of the bile acids secreted are reabsorbed from the intestines and returned via the portal circulation to the liver, thus completing the enterohepatic cycle (Marier et al, 2002).…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…Extremely rapid sulfate conjugation by the intestine/liver appears to be the ratelimiting step in t-RVT bioavailability. Second peak at 2 h indicates enterohepatic recirculation of the drug that has been well documented and enterohepatic recirculation is susceptible to circadian variation (Almeida et al, 2009) (as is evident from Figure 4 where two peaks of C max and T max were observed). A major portion of the bile acids secreted are reabsorbed from the intestines and returned via the portal circulation to the liver, thus completing the enterohepatic cycle (Marier et al, 2002).…”
Section: Discussionmentioning
confidence: 84%
“…Group I received OPT formulation and Group II received the pure drug in the form of 0.3% carboxymethyl cellulose suspension. All the animal groups received a dose equivalent to 20 mg of t-RVT per kg of body weight (Almeida et al, 2009;. Following oral drug administration, the rats kept in the cages were allowed access to food and water ad libitum.…”
Section: In Vivo Pharmacokinetic Studies In Ratmentioning
confidence: 99%
“…Similarly, Chow et al found plasma resveratrol concentration to range from 8.3 to 404.4 mg/L 1 h following 1 g resveratrol supplementation [31]. C max can be increased through multiple days of supplementation [32]. Almeida et al [32] administered 13 doses of 25, 50, 100, and 150 mg trans-resveratrol at 4-h intervals to 4 respective groups of 8 healthy subjects and compared plasma resveratrol concentration following the first and last (13th) dose.…”
Section: Bioavailability From Resveratrol Supplementsmentioning
confidence: 91%
“…C max can be increased through multiple days of supplementation [32]. Almeida et al [32] administered 13 doses of 25, 50, 100, and 150 mg trans-resveratrol at 4-h intervals to 4 respective groups of 8 healthy subjects and compared plasma resveratrol concentration following the first and last (13th) dose. C max more than doubled in the 25 and 150 mg group between the first and thirteenth dose, although this was not observed with the 50 and 100 mg groups.…”
Section: Bioavailability From Resveratrol Supplementsmentioning
confidence: 99%
“…The trans form is able to undergo isomerization into the cis form upon exposure to ultraviolet irradiation (9). Although the two isomers often exist in combination, the trans form is more biologically active and more frequently investigated (8,9,17,18). Red wine is known to contain a high concentration of trans-resveratrol.…”
Section: Introductionmentioning
confidence: 99%